2009
DOI: 10.1016/j.brainres.2009.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Saccade trajectories evoked by sequential and colliding stimulation of the monkey superior colliculus

Abstract: Using microstimulation we employed explicit experimental control of activity in the superior colliculus at two sites within the motor map. We compared saccade metrics and dynamics evoked at each site independently with those caused by sequential presentation and collisions of the two stimulation trains. Essentially, we forced controlled spatio-temporal patterns of activity into the saccade control circuit with various timing relationships from known sites within the collicular motor map, thus revealing the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…We furthermore observed that the majority of targeting saccades executed shortly after an OKN fast-phase were curved in the direction of that fast-phase, and that after 100ms this effect decayed away to the point at which saccades curved roughly equally in and against the direction of OKN fast-phases. This is in line with what is known about the time course of SC activity and curvature: for two sites of activity in the SC to elicit saccade curvature they must occur in close temporal proximity (Noto & Gnadt, 2009). …”
Section: A Role For the Superior Colliculus In Okn Fast-phases?supporting
confidence: 89%
“…We furthermore observed that the majority of targeting saccades executed shortly after an OKN fast-phase were curved in the direction of that fast-phase, and that after 100ms this effect decayed away to the point at which saccades curved roughly equally in and against the direction of OKN fast-phases. This is in line with what is known about the time course of SC activity and curvature: for two sites of activity in the SC to elicit saccade curvature they must occur in close temporal proximity (Noto & Gnadt, 2009). …”
Section: A Role For the Superior Colliculus In Okn Fast-phases?supporting
confidence: 89%
“…Stimulation-evoked saccades that interacted with the visual target showed no obvious signs of curvature (saccades directed first toward one target and then toward the other in midflight; Arai et al 2004;Port and Wurtz 2003) and reflected a weighted combination of the visual and stimulation-evoked saccades; only this subset of movements was analyzed for the purpose of this study. Saccades observed on other trials clearly resembled pure stimulation movements (stimulation onset occurred well before the visually guided saccade), curved saccades (stimulation onset occurred during the visually guided saccade), or pure visual movements (stimulation onset occurred after the visually guided saccade) (McPeek et al 2003;Noto and Gnadt 2009) and were excluded from additional analyses. We note that movement of this nature were rarely observed during each session (Ͻ1% of data removed) because the stimulation onset spanned a narrow temporal range.…”
Section: Experimental Procedures and Behavioral Tasksmentioning
confidence: 99%
“…Recent dual microstimulation experiments in the oculomotor system have employed temporal shifts between the stimulation trains elicited at each electrode. Noto and Gnadt (2009) evaluated the generation of curved saccades, whereas Brecht et al (2004) attempted to differentiate between VA and VS. Our analysis of endpoint distributions provides a systematic and in-depth analysis of the long-standing but poorly tested weighted VA hypothesis, which is necessary to link averaging saccades across literature in the oculomotor field.…”
Section: Previous Studies Using Dual Microstimulation In the Oculomotmentioning
confidence: 99%